The IMPACT OF COVID-19 PANDEMIC ON LEARNING OF UNDERGRADUATE MEDICAL STUDENTS: A CROSS-SECTIONAL STUDY FROM KARACHI - Anwar, Adina; Khan, Erum; Nisar, Munizha; Din, Rameesha Qutub ud; Azim, Syed Rubaba; Awan, Tamseel Tanwir (Pakistan Armed Forces Medical Journal, 2020)
Objective: To assess the impact of COVID-19 pandemic on learning of undergraduate medical students of Karachi. Study Design: A cross-sectional, observational study. Place and Duration of Study: Study was conducted at conducted at the different public and private medical colleges, Karachi, from Mar to Apr 2020. Methodology: Google survey form based cross-sectional study conducted at the different public and private medical colleges, Karachi from March till April 2020. Non-probability consecutive sampling technique was used. This questionnaire consisted of 13 items which focused on the impact of COVID-19 pandemic on the learning of undergraduate medical students from Karachi. Results: The study was conducted on 110 undergraduate students. Out of which, majority of the participants were from third year 45 (41%) and second year of MBBS 25 (23%). It was found that almost 71% of the undergraduate students had less likely to remember and understand material taught in online class and 60% had less likely to get answers to their queries as compared to regular classes. The results also showed that 49% of the undergraduate students were disturbed by technical issues during online classes. Furthermore, it was also found that learning of 54 out of 110 undergraduate students was always affected due to loss of clinical rotations. Strong association were also found in between online satisfaction and stressful condition due to online classes. Conclusion: It was concluded that COVID-19 pandemic greatly affected the learning of the undergraduate medical students and have negatively impacted their satisfaction level towards their studies.